Disease-associated KIF3A variants alter gene methylation and expression impacting skin barrier and atopic dermatitis risk - Mariana L. Stevens (Nature Portfolio, 2020)
Genetic variants in KIF3A are associated with atopic dermatitis (AD). Here, the authors identify two AD-risk alleles that show high methylation resulting in lower KIF3A expression. Mice with epidermis-specific loss of Kif3a show disrupted skin barrier homeostasis and increased AD susceptibility.